Management of rare malignant neoplasms during pregnancy - Reyna-Villasmil, Eduardo (2021)
Cancer during pregnancy occurs in 0.07% to 0.1% of all pregnancies. Due to the marked increase in maternal age at delivery, the incidence of malignant tumors diagnosed during pregnancy has increased. Although it is a rare condition, it must be identified and treated immediately, since pregnancy can produce conflicts for maternal treatment and optimal fetal development. The most common cancers during pregnancy are breast, cervical, melanoma, leukemia and lymphoma. However, there are less frequently reported cases of the pancreas, kidney, adrenal glands, bladder, lung, hepatobiliary, vulva, and central nervous system. Lack of experience and knowledge could lead to late diagnosis, imprecise treatment, and maternal-fetal complications. Cancer treatment strategies during pregnancy should not differ significantly from treatment regimens in non-pregnant women. The decision about the initiation and continuation of treatment should be preceded by a detailed analysis of the possible benefits and risks. Therefore, it is necessary to take into account diagnostic guidelines and weigh fetal safety with a multidisciplinary approach to establish potential therapeutic options.